Epigenetic activation of FOXF1 confers cancer stem cell properties to cisplatin-resistant non-small cell lung cancer - Zhao, Jian (Int J Oncol, 2020)
The underlying molecular mechanisms of cisplatin resistance in non-small cell lung cancer (NSCLC) are unclear. In this study, a novel differential methylation region located in the upstream regulatory region of the forkhead box F1 (FOXF1) gene was identified. The abnormal hypomethylation of FOXF1 increased the expression of FOXF1, and the high expression of FOXF1 promoted cell proliferation and inhibited cell apoptosis induced by cisplatin, which resulted in cisplatin resistance in NSCLC cells. In addition, FOXF1 promoted the expression of stem cell markers and self-renewal capability, indicating that FOXF1 regulated cisplatin resistance by promoting cancer stem cell properties in NSCLC cells. Moreover, a strong association was observed between FOXF1 upregulation and the presence of platinum-based chemotherapy resistance in patients with NSCLC. On the whole, the findings of this study indicate the regulatory mechanisms of cisplatin resistance by FOXF1 in NSCLC, and suggest that FOXF1 may be used as a prognostic biomarker of platinum-based chemotherapy resistance in NSCLC.